A preliminary study on effects of mobile phone radiation to human brainwave using EEG / Roshakimah Mohd Isa - Mohd Isa, Roshakimah (2010)
The aim of this research is to determine whether there are any effects of mobile phone radiation to human brainwave using electroencephalograph (EEG) and how will be the alpha wave pattern due to the mobile phone radiation. EEG recording will be taken from thirty awaked samples from Faculty of Electrical Engineering aging from 19 to 28 years old. These samples will be exposed to radiation or radiofrequency (RF) emissions from a mobile phone positioned at right ear. Three experimental designs will be conducted which are before, during and after the exposure to the radiation. Samples will be interviewed with questions related to the topic before they proceed with EEG test. Then the results of captured brainwave signals were analyzed and comparisons between the three states were discussed. In conclusion, after being exposed to the radiation, alpha wave signal was decreased as compared to the other three waves. This is in line with finding of a survey studied by Santini et al. in France found mobile phone radiation may be causing short and long term effect such as headache and loss of memory.